Re-tubularization of highly-ischemic anti-mesenteric border (ReHAB) - Joseph J. Lopez; Richard J. Hendrickson (Elsevier, 2021)
Complex gastroschisis and other etiologies of intestinal compromise present a difficult medical and surgical challenge in the neonatal and pediatric population. Aggressive resection of intestinal length in these cases can lead to significant short bowel syndrome and prolonged or lifelong dependence on parenteral nutrition. This method of bowel preservation previously described has led to additional patients achieving enteral autonomy and we present their cases and most recent outcomes.